2004
DOI: 10.1002/hep.20031
|View full text |Cite
|
Sign up to set email alerts
|

MUC4 is a novel prognostic factor of intrahepatic cholangiocarcinoma-mass forming type

Abstract: Complete surgical resection of the tumor is the sole approach to improve the cure rate of patients with intrahepatic cholangiocarcinoma-mass forming type (ICC-MF). Although patients are treated by curative resection, many of them show poor outcome. Mucin (MUC)4 expression has been implicated as a marker for diagnosis and progression of pancreatic adenocarcinomas, but there is no study of the relationship between MUC4 expression and patient's prognosis in ICC-MF. In the present study, we examined the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
122
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 45 publications
9
122
1
1
Order By: Relevance
“…The evidence that Muc4 potentiates HER2 signaling has led to the hypothesis that it may promote HER2 tumorigenic signaling even in tumors that do not overexpress HER2. Consistent with this hypothesis, increased expression of Muc4 is associated with worse prognosis in several types of cancer (Shibahara et al, 2004;Saitou et al, 2005;Tamada et al, 2006;Tsutsumida et al, 2006). Further analysis of this hypothesis awaits models that more definitively demonstrate the role of Muc4 in promoting tumorigenic HER2 function.…”
Section: Cell Cycle Deregulationmentioning
confidence: 72%
“…The evidence that Muc4 potentiates HER2 signaling has led to the hypothesis that it may promote HER2 tumorigenic signaling even in tumors that do not overexpress HER2. Consistent with this hypothesis, increased expression of Muc4 is associated with worse prognosis in several types of cancer (Shibahara et al, 2004;Saitou et al, 2005;Tamada et al, 2006;Tsutsumida et al, 2006). Further analysis of this hypothesis awaits models that more definitively demonstrate the role of Muc4 in promoting tumorigenic HER2 function.…”
Section: Cell Cycle Deregulationmentioning
confidence: 72%
“…In CC, however, four groups have examined HER-2/neu expression using IHC and found no correlation with survival (61,62,74,75).…”
Section: Epidermal Growth Factor Receptor (Egfr) Familymentioning
confidence: 99%
“…Of the nine studies that have examined the prognostic value of MUC1 in CC, all except one have demonstrated a significant correlation between MUC1 expression and decreased survival, both on univariate and multivariate survival analyses (61,62,(101)(102)(103)(104)(105)(106)(107).…”
Section: Muc1mentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry for the detection of alpha-fetoprotein, alpha-1-antitrypsin, different types of cytokeratins (CKs), hepatocyte-specific antigen (HSA) and other markers-as syndecan-1, tenascin, mucin 1 and 4, b-catenin alteration-might help in establishing the correct diagnosis or to determine the prognosis. [5][6][7][8][9][10] Tight junctions, the most apical part of the intercellular junctional complex, play an essential role in maintaining cell polarity and determining paracellular permeability in organs of epithelial origin. 11,12 Cell adhesion, polarity and intercellular communication are especially important in the trabecular structure of the liver and in the formation of the bile duct system, where tight junctions separate bile flow from plasma.…”
mentioning
confidence: 99%